Constitutional Review and Minority Rights: Aligning Domestic Courts with International Norms - Syaefudin, Rochmat Ali (Legalis : Journal of Law Review, 2024)
The protection of minority rights is central to democratic governance and international human rights law. This article examines how constitutional review mechanisms interact with international normative frameworks to shape outcomes for ethnic, religious, and linguistic minorities in democratic states. Drawing on the International Covenant on Civil and Political Rights (ICCPR), the UN Declaration on Minorities, and the Council of Europe Framework Convention, the study outlines the legal obligations imposed on states. Through a comparative doctrinal and institutional analysis of Germany, India, South Africa, the United States, and the European Court of Human Rights, it evaluates the effectiveness of different constitutional review models. Data from the Comparative Constitutions Project and landmark case law illustrate the significance of institutional design particularly centralized review and individual complaint mechanisms in enabling courts to enforce minority protections. The discussion highlights the importance of institutional strength, alignment with international norms, resistance to political interference, and transjudicial dialogue in sustaining robust protections. The article concludes that judicial effectiveness in minority rights adjudication hinges on coherent legal frameworks, empowered institutions, and principled jurisprudence that resonates with international human rights standards.